Nanostructurization of Si and GaAs by acoustic cavitation in liquid nitrogen - Savkina, R.K.; Smirnov, A.B. (Reports of the National Academy of Sciences of Ukraine, 2015)
The properties of the Si and GaAs samples subjected to cavitation impacts have been studied. It is shown that the high-intensity (15 W/cm2) high-frequency (1÷6 MHz) sonication in liquid nitrogen induces changes of the physical, chemical, and structural properties of the semiconductor surface. The optic and atomic force microscopy techniques, as well as energy dispersive X-ray spectroscopy and photoresponse spectroscopy, are used. The experimental study demonstrates the nanostructure formation and a change of the chemical composition at the semiconductor surface. It is found that a significant rise in the value and the expansion of a spectral range of photosensitivity take place after the cavitation treatment.